Comparison of Clinical Features in Hla-B27 Positive and Negative Patients with Axial Spondyloarthritis - Shaukat, Hassan; Fakhr, Amer; Tasleem, Zohra; Abbas Niazi, Ghulam; Khurshid, Amina; Hakim, Farzana (Pakistan Armed Forces Medical Journal, 2025)
Abstract Objective: To compare the clinical features of HLA-B27 positive and negative patients having axial spondyloarthritis. Study Design: Qusai-experimental study. Place and Duration of Study: Department of Rheumatology, Pak Emirates Military Hospital (PEMH), Rawalpindi Pakistan, from Oct 2022 to Apr 2023. Methodology: Patients with axial spondyloarthritis who were diagnosed by consultant rheumatologist on the basis of Assessment of Spondyloarthritis International Society were recruited. All baseline investigations and HLA typing were performed on the study participants. They were further divided into two groups for comparison on the basis of HLA-B27 positivity or negativity. Relevant clinical features were compared in both the groups. Results: A total of 150 patients of axial spondyloarthritis were recruited in this study, with mean age being 42.78±10.2 years, among whom 41(27.3%) patients were female while 109(72.7%) were male, while 104(69.3%) patients of axial spondyloarthritis were HLA-B27 positive and 46(30.7%) were HLA-B27 negative. It was noted that positive family history of axial spondyloarthritis, hip joint involvement, uveitis, inadequate response to NASAIDs and good response to biological therapy were statistically significant among patients who were HLA-B27 positive as compared to those who were HLA-B27 negative. Conclusion: Positive family history, hip joint involvement, uveitis, inadequate response to NASAIDs and good response to biological therapy was noted among patients who were HLA-B27 positive.